Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean) - Valdés, Ángel; Cadien, Donald B.; Gosliner, Terrence M. (Zootaxa, 2016)
Based on morphological data a total of nine native species of Philinidae are recognized from the northeastern Pacific including the Bering Sea and the adjacent Arctic Ocean (Beaufort Sea). Four of them have been previously described: Philine ornatissima Yokoyama, 1927, Philine bakeri Dall, 1919, Philine polystrigma (Dall, 1908), and Philine hemphilli Dall, 1919. Five of them are new and described herein: Philine mcleani sp. nov., Philine baxteri sp. nov., Philine malaquiasi sp. nov., Philine wareni sp. nov., and Philine harrisae sp. nov. These species display a substantial degree of variation in internal and external morphological traits (i.e., presence/absence of gizzard plates, different radular structure and tooth morphology, various reproductive anatomical features) and it is likely that they belong to different clades (genera). However, in the absence of a comprehensive phylogeny for Philine, they are here provisionally regarded as Philine sensu lato. In addition to the nine native species, two introduced species: Philine orientalis A. Adams, 1854 and Philine auriformis Suter, 1909 are here illustrated and compared to the native species to facilitate identification. Finally, two species previously considered members of Philinidae are examined anatomically and confirmed as members of Laonidae, Laona californica (Willett, 1944) and Philinorbidae, Philinorbis albus (Mattox, 1958), based on morphological data.